Multivalued Extended Best Φ-Polynomial Approximation Operator. (1st November 2016) - Acinas, Sonia; Favier, Sergio
ABSTRACT: In this article, we consider the best multivalued polynomial approximation operator, defined in an Orlicz Space L Φ ( B ), and its extension to L φ ( B ), where φ is the derivative of Φ which is not an N -function. Thus, the extension of the best polynomial approximation operator from L 1 ( B ) to L 0 ( B ) arises as a particular case of this work, taking Φ ( x ) =  x .